The migrant and refugee entrepreneur (of the self): vernacular modes of immaterial labor as (re)invention of the self in the destination country - Laura Alves Scherer1; Carmem Ligia Iochins Grisci (BBR: Brazilian Business Review)
This article adopts the Autonomy of Migration approach to analyze the singularization of migrants and refugees from creating work activities based on the perspective of immaterial labor. The cartographic method was used to collect data from interviews and participant observation in Porto Alegre (Brazil), exploring events-activities, key informants, and economic migrants and refugees from the global south who work with music, dance, food, fashion, language, and political-cultural representation. The findings show that the mobilization of migrants and refugees in a cooperation network stresses the vernacular references and the migration/refuge situation, making them entrepreneurs of themselves. A mode of singularization is perceived regarding a labor market for migrants and refugees linked to affection and politics, which allows, through immaterial labor, the (re)invention of the self in the destination country.